Responsabilidad penal por incendios forestales en el cantón Chilla, periodo 2013-2014. - Chuchuca Chuchuca, Jaime Rodrigo (2015)
The constitution of the Republic of Ecuador protects the right of society. Beside confers protection inmediatly to the nature granting it rights, Al this obviously for the protection of the ecosystem in which we are frame all the ecuadorians. The protection to the nature is completed in a direct way with actions of protections and preventive measures of administrative authority and control but when the infringement has been caused as in the case of forest fires , we have the organic penal integral code to establish the procedures and penalties which it should submit to the reponsable of those acts . The crime of wildfire is not a recent invention of legislators as its antecedent we found in ancient laws and codes and whose sanctions were drastic in some cases were sanctioned with the burning of the person who caused such fires. Some peoples typified to protect the agricultural properties that at the time was the main activity of man and hence perhaps it could understand the harshness of penalties in some places of the ancient world. Long time had to move the criminal typification of wildfire for harsh punishments of yesteryear are minimized to less penalties prison and perhaps it is because agriculture is no longer the most important activity of the man. Since the diversity of activities of today's world turn allows the establishment of penalties according to the need of legal properties to be protected.The constitution of the Republic of Ecuador protects the right of society. Beside confers protection inmediatly to the nature granting it rights, Al this obviously for the protection of the ecosystem in which we are frame all the ecuadorians. The protection to the nature is completed in a direct way with actions of protections and preventive measures of administrative authority and control but when the infringement has been caused as in the case of forest fires , we have the organic penal integral code to establish the procedures and penalties which it should submit to the reponsable of those acts . The crime of wildfire is not a recent invention of legislators as its antecedent we found in ancient laws and codes and whose sanctions were drastic in some cases were sanctioned with the burning of the person who caused such fires. Some peoples typified to protect the agricultural properties that at the time was the main activity of man and hence perhaps it could understand the harshness of penalties in some places of the ancient world. Long time had to move the criminal typification of wildfire for harsh punishments of yesteryear are minimized to less penalties prison and perhaps it is because agriculture is no longer the most important activity of the man. Since the diversity of activities of today's world turn allows the establishment of penalties according to the need of legal properties to be protected.